Comparative Analysis of Plastid Genomes in the Non-photosynthetic Genus Thismia Reveals Ongoing Gene Set Reduction - Yudina, Sophia V.; Schelkunov, Mikhail I.; Nauheimer, Lars; Crayn, Darren; Chantanaorrapint, Sahut; Hroneš, Michal; Sochor, Michal; Dančák, Martin; Mar, Shek-Shing; Luu, Hong Truong; Nuraliev, Maxim S.; Logacheva, Maria D. (Frontiers in Plant Science, 2021)
Heterotrophic plants provide intriguing examples of reductive evolution. This is especially evident in the reduction of their plastid genomes, which can potentially proceed towards complete genome loss. Several milestones at the beginning of this path of degradation have been described; however, little is known about the latest stages of plastome reduction. Here we analyze a diversity of plastid genomes in a set of closely related non-photosynthetic plants. We demonstrate how a gradual loss of genes shapes the miniaturized plastomes of these plants. The subject of our study, the genus Thismia, represents the mycoheterotrophic monocot family Thismiaceae, a group that may have experienced a very ancient (60–80 mya) transition to heterotrophy. In all 18 species examined, the plastome is reduced to 14–18 kb and is highly AT-biased. The most complete observed gene set includes accD, seven ribosomal protein genes, three rRNA, and two tRNA genes. Different clades of Thismia have undergone further gene loss (complete absence or pseudogenization) compared to this set: in particular, we report two independent losses of rps2 and rps18.